(3eONd Gdi GdeMGSHI GdYGeI (B-(3OQhS hCYeGd ehLgI(B-s - (3fGUQ(B, (3eQRhbs ((3GdLRGFQ(B:s (3GdUaMGJ GdRQbGA GdYGdejI(B,s, 2008)
(3GdeDSSI, eONd Gdi GdeMGSHI GdYGeI, GdejRGfjI, GdMSGH, CfXeI GdJSLjd GdeMGSHj, GdjhejI GdYGeI, OaJQ GdCSJGO, ejRGf GdeQGLYI, Mdhd GdCYeGd GdehLgIs
(3HHdjhZQGajG(B: (3U(B.109s
Keywords: (3GdeMGSHIs; (3GdejRGfjIs